Case Report: Capacity to Objectively Monitor the Response of a Chronic Pain Patient to Treatment - Watson, Julia; Lukas, Darren; Vickers, E. Russell; Galloway, Graham; Mountford, Carolyn E. (Frontiers in Neuroimaging, 2022)
Response to pain therapy is currently by patient self-report. We demonstrate that by evaluating the neurochemistry of a patient, using two-dimensional Correlated SpectroscopY (2D COSY) in a 3T MRI scanner, response to therapy can be recorded. A chronic temporomandibular joint (TMJ) pain patient was evaluated by a pain physician specializing in temporomandibular disorders (TMD), and by 2D COSY, before, and 6 days after treatment with Botulinum Toxin A. Prior to treatment the self-reported pain score was 8/10 and reduced to 0/10 within 24 h of treatment. The neurochemistry of the patient prior to treatment was typical of chronic pain. In particular, the Fuc-α(1–2) glycans were affected. Following treatment, the substrates, α-L Fucose, were elevated and the Fuc-α(1–2) glycans repopulated. The depletion of the molecule assigned the glutathione cysteine moiety, with chronic pain, is indicative of a Glutathione redox imbalance linked to neurodegeneration. This new approach to monitor pain could help discriminate the relative contributions in the complex interplay of the sensory and affective (emotional suffering) components of pain leading to appropriate individualized pharmaceutical drug regimens.